P266 A case of mixed fungal infection causing invasive fungal Rhinosinusitis in a post-COVID patient. (20th September 2022) - Ray, Ujjwayini; Dutta, Soma
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objectives: To identify the fungal etiology of invasive nasal sinusitis in a patient of post-COVID. Methods: A 34-year-old non-diabetic man, who had mild coronavirus disease (COVID) infection 2 months back presented with left-sided nasal obstruction, headache accompanied by malodorous, thick, mucopurulent discharge for the last 2 weeks. A CT scan of sinuses revealed opacification of left posterior ethmoid and sphenoid sinus without bony erosion or calcification. The patient underwent unilateral functional endoscopic sinus surgery (FESS) and debridement of tissue from the affected sinuses. Results: A KOH preparation of the debrided tissue showed thin septate hyphae. Gram-stained smear of the debrided material showed thin septate fungal hyphae with clamp-like connections (Fig. 1). Histopathological examination revealed features of the inflammatory polyp. In Sabouraud dextrose agar the fungal colony grew fast and its aerial mycelium is white and cotton-like. The fungus was phenotypically identified as Schizophyllum communae (identification was confirmed at the National Reference Centre). He continued to do well but about 2 months later he started experiencing headaches and pain behind the eyes. He also complained of nasal stuffiness (left greater than right) and yellowish nasal discharge. At this point, a CT scan revealed soft tissue density with interspersed hyperdensity in sphenoid sinus bilateral ethmoid, and bilateral maxillary sinuses with associated bony erosion and possible extension into the right cavernous sinus and extrachonal compartment of right orbit suggestive of invasive fungal sinusitis (Fig. 2). Bilateral FESS was done. Extensive fungal material was observed in the sphenoid sinus and thorough debridement was performed. Mycological studies of the debrided tissue showed thin septate hyphae. Schizophyllum communae was again isolated in culture. Histopathological section showed inflammatory cells and several slender, branching septate fungal hyphae. The invasive nature of the infection prompted reexamination of the histopathology slides and cultures for the presence of other fungi particularly of the Mucorales group but no other fungus could be identified. The patient was started on liposomal amphotericin B and the tissue blocks were sent for fungal identification to the National Reference Centre through sequencing following DNA extraction from the paraffin blocks. Amplification of the 18 S rDNA region (coding for the 18 S RNA) using ZM primers followed by sequencing revealed the presence of R. arrhizus . The patient was continued on amphotericin B. The patient was discharged after 2 weeks with oral isuvuconazole. At six months follow up he is doing well with no evidence of active infection Conclusion: As the novel COVID‐19 continues to rampage, an abrupt increase in the number of opportunistic fungal infections has been observed. Invasive and often fatal rhino-cerebral Mucormycosis is now been increasingly reported in patients who have had COVID-19 infection in the recent past. In this case, there was a dual fungal infection causing rhino-sinusitis which was established through conventional culture and PCR assays from paraffinized tissue sections. Increased awareness of the existence of dual mold infections in at-risk patients is necessary for optimum management. PCR methods in tissue sections increase the diagnosis of dual mold infections.